Effectiveness of written action plans for acute asthma: A systematic review. (1st February 2018) - Villa-Roel, Cristina; Voaklander, Britt; Ospina, Maria B.; Nikel, Taylor; Campbell, Sandra; Rowe, Brian H.
ABSTRACT: Objective : Self-management is an essential part of achieving asthma control and improving long-term outcomes. While guidelines recommend the provision of written asthma action plans (AAPs), few patients presenting to emergency departments (ED) have one. This systematic review examined if individualized written AAPs reduce relapses in adults following an ED visit for acute asthma. Data sources : Comprehensive searches of seven electronic databases and grey literature were conducted. Study selections : Randomized controlled trials (RCTs) examining the effectiveness of individualized written AAPs to reduce relapses after ED visits for acute asthma were included. Study quality was determined using the Cochrane Risk of Bias (RoB) tool; intervention fidelity was assessed. Results : From 695 potentially relevant studies, three RCTs were included. The RoB was low in two studies and high in one study; description of intervention fidelity varied across studies. The provision of individualized written AAPs in adults following an ED visit for acute asthma did not reduce the risk of relapse after ED discharge (risk ratio [RR] = 0.66; 95% confidence intervals [CI]: 0.36, 1.23; I 2 = 40%). There was a 49% reduction in the risk of relapse after ED discharge when only studies with low RoB were pooled (RR = 0.51; 95% CI: 0.31, 0.83; I 2 = 0%). Conclusion : This review did not provide conclusive evidence to support the consideration of individualized written AAPs for the reduction of relapses after an ED visit; however, the low frequency of events, small number of studies and samples, and their methodological quality might play an important role in this overall finding.